An Inverse Boundary Value Problem for a Second Order Elliptic Equation in a Rectangle - Mehraliyev, Yashar T.; Kanca, Fatma (Mathematical Modelling and Analysis, 2014)
In this paper, the inverse problem of finding a coefficient in a second order elliptic equation is investigated. The conditions for the existence and uniqueness of the classical solution of the problem under consideration are established. Numerical tests using the finite-difference scheme combined with an iteration method is presented and the sensitivity of this scheme with respect to noisy overdetermination data is illustrated.